2007
DOI: 10.1016/j.gca.2006.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Transformations of mercury, iron, and sulfur during the reductive dissolution of iron oxyhydroxide by sulfide

Abstract: Methylmercury can accumulate in fish to concentrations unhealthy for humans and other predatory mammals. Most sources of mercury (Hg) emit inorganic species to the environment. Therefore, ecological harm occurs when inorganic Hg is converted to methylmercury. Sulfate-and iron-reducing bacteria (SRB and FeRB) methylate Hg, but the effects of processes involving oxidized and reduced forms of sulfur and iron on the reactivity of Hg, including the propensity of inorganic Hg to be methylated, are poorly understood.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(30 citation statements)
references
References 95 publications
0
28
2
Order By: Relevance
“…Second-neighbor Hg–Fe distances in both samples (3.46 and 3.49 Å) were slightly longer than the Hg–Fe distance (3.40 Å) reported previously for Hg sorption on goethite in one study. 42 These Hg–Fe distances are significantly longer than the Hg–Fe distances (3.19–3.29 Å) reported in other studies for Hg complexes on goethite surfaces. 25,26,43 These prior studies have attributed the observed differences in Hg–Fe distances to the presence of monodentate (longer distance) and bidentate (shorter distance) inner-sphere sorption complexes on goethite.…”
Section: Discussionmentioning
confidence: 60%
“…Second-neighbor Hg–Fe distances in both samples (3.46 and 3.49 Å) were slightly longer than the Hg–Fe distance (3.40 Å) reported previously for Hg sorption on goethite in one study. 42 These Hg–Fe distances are significantly longer than the Hg–Fe distances (3.19–3.29 Å) reported in other studies for Hg complexes on goethite surfaces. 25,26,43 These prior studies have attributed the observed differences in Hg–Fe distances to the presence of monodentate (longer distance) and bidentate (shorter distance) inner-sphere sorption complexes on goethite.…”
Section: Discussionmentioning
confidence: 60%
“…This is caused by several factors affecting mercury methylation and fish mercury bioaccumulation. Primary factors affecting mercury methylation are spatiotemporal variation in quality and quantity of DOC (Cai et al 1999; Benoit et al 2001; Reddy and Aiken 2001; Drexel et al 2002; Miller et al 2007), bioavailable inorganic mercury (Benoit et al 1999a, b; Kelly et al 2003), redox conditions (Marvin-DiPasquale et al 2003; Hollweg et al 2009), concentration of other dissolved ions (Jay et al 2002; Slowey and Brown 2007), and pH (Kelly et al 2003). Primary factors affecting mercury bioaccumulation are water temperature (Bodaly et al 1993; Ethier et al 2008), fish feeding patterns (Li et al 2009; Riva-Murry et al 2011), growth rates (Simoneau et al 2005), and migration (Eagles-Smith et al 2008; Baker et al 2009).…”
Section: Resultsmentioning
confidence: 99%
“…This avenue can be explored in future studies of environmental Spartina samples. Precipitation of HgS has also been seen in conditions mimicking the presence of SRB and FeRB (15). The precipitated HgS would most likely be in the form of metacinnabar, the main product of Hg precipitation with sulfides.…”
Section: Discussionmentioning
confidence: 99%